Assessment of nutritional status of the patient with cancer of the stomach by means of selected methods of anthropometric, biochemical and immunological - Monika Pierzak; Aneta Chrut; Martyna Gorzelak (Kazimierz Wielki University, 2018)
Introduction: Nutritional status is a medical condition that results from the customary intake of food absorbed and the use of its component nutrients or non-nutrients. Malnutrition is a problem faced by therapeutic teams around the world. This condition affects approximately 20-50% of patients hospitalized au deepens 30-90% of patients during hospital treatment. Aim: Assessment of nutritional status of a patient with gastric cancer using selected methods of anthropometric, biochemical and immunological research. Material and methods: The patient admitted in the surgery ward elective 64 years, diagnosis of gastric cancer according to the TNM classification type T3N1MO for treatment. A patient with a history of three cycles of neoadjuvant chemotherapy. Results: Taking into account the results of the questionnaire NRS-2002, interview, physical examination, symptoms, anthropometric measurements, biochemical and immunological studies can assess the nutritional status of the patient is not valid. The patient is malnourished. Taking into account the recommendation ESPEN (Europan Society for Paraenteral and enteral nutrition) and nutritional status of the patient has become necessary to incorporate nutritional therapy. The patient was included in parenteral nutritional therapy. Conclusions: Malnutrition is a medical condition rarely recognized, in consequence of which comes to many dangerous health complications discouraging and even the life of the patient. There are several types of malnutrition. Often, patients with cancer, particularly cancer of the gastrointestinal tract, resulting in prolonged malnutrition, cachexia occurs. Cachexia is a syndrome due to systemic inflammatory response which is a response to the presence of the disease in the body. Recognized malnutrition should be treated. After identifying the patient at risk of malnutrition or who is in the disease state of malnutrition, are introduced nutritional therapy. Evaluation of nutrition should belong to the basic skills of each member of the therapeutic team.